The development of an islamic nursing care model to improve patient satisfaction - Ardian, Iwan; Nursalam, Nursalam; Ahsan, Ahsan; Haiya , Nutrisia Nu’im; Azizah , Intan Rismatul (Jurnal Ners, 2024)
Introduction: This study aimed to the development of an Islamic nursing care model to improve patient satisfaction. Methods: Cross-sectional design random sampling technique on 134 respondents, consisting of patients and nurses in the surgical inpatient room, internal medicine inpatient room, and postpartum and gynecology inpatient rooms, using simple random techniques. The variables of this study were the nursing factors, Islamic nursing care, and patient satisfaction and were collected using questionnaire. The data were collected using questionnaire in December 2021 at Islamic Hospital, Indonesia, and processed using a Smart Partial Least Squares (SmartPLS) analysis and Sommers’ correlation test. Results: The Sommers’ test results show significant relationship between nursing factor (nurse knowledge, nurse’s attitude, nurse competence, nurse personality) and patient satisfaction; nurse knowledge (p=0.000); nurse attitude (p=0.000); nurse competence (p=0.000); nurse personality (p=0.000; α<0.05). SmartPLS test results show the nurse factor with Islamic nursing care has a strong significant influence (p value 0.000; β value 0.539; t value> 1.96). Then for Islamic nursing care with patient satisfaction, it has a very strong significant effect (p value 0.000; β value 0.753; t value> 1.96). Conclusions: Islamic nursing care as a mediator of nurse factors with patient satisfaction can be described in this study model because Islamic nursing care is a real form of care by nurses that is felt by the patient and the application of Islamic values so that the form of nursing care makes patients feel satisfied.